Autonomy of Toddler-Age Children in the Nursery and the Family - Coza, Maria-Madalina (Technium Social Sciences Journal, 2026)
Autonomy in early childhood is frequently addressed in the scholarly literature in a reductive manner, being predominantly associated with functional independence or early behavioral acquisitions. The present article proposes a conceptual and theoretical clarification of autonomy in the 0–3 age range, arguing that it represents an emergent, relational, and deeply contextual process. The analysis integrates contributions from developmental psychology, the sociology of childhood, and motivational theories, with a particular focus on Self-Determination Theory, in order to highlight the multidimensional nature of autonomy (functional, socio-emotional, relational, and motivational). The article examines autonomy as the outcome of children’s everyday interactions with their primary developmental contexts—the family and the nursery—emphasizing the role of attachment relationships, self-regulatory processes, social participation, and the educational climate in shaping autonomous behaviors. Within this framework, autonomy is conceptualized not as the opposite of dependence, but as the product of sensitive relationships, predictable routines, and contexts that recognize and support children’s initiative. Through this integrated approach, the article provides a coherent theoretical framework for interpreting young children’s autonomy and argues for moving beyond an instrumental–functional perspective in the analysis of early childhood education.